Possible psychosocial impacts on women before domestic violence (Research, Society and Development, 2022)
The present study aims to describe the possible psychosocial impacts caused on women in the face of domestic violence. It is an epidemiological, exploratory study with a quantitative approach that used a literature review to deepen the theme, on the platform of the Department of Informatics of the Unified Health System of Brazil present in the Information System of Notifiable Diseases, extracting the data of violence in recent years from 2018 to 2021, such as the articles made available in full on the Scientific Electronic Library Online platform and the Virtual Health Library. From the studies carried out, it was possible to perceive that according to the World Health Organization about 30% of women in the world have already been victims of violence by their marital partners. In Brazil, there was a rate of 43% for physical violence, 13% for sexual and 27% for psychological violence. In view of the data collected in the Notifiable Diseases Information System in the period from 2018 to 2021 in Brazil, the registered notifications of violence by age group from 15 to 60 ≥ years were extracted, such as race, gender, region of notification, education and the types of violence. It is notorious that domestic violence negatively affects women, not only physically but also psychologically, which ends up generating traumas that can perpetuate throughout life, impacting the quality of life of these women, both in the social, spiritual, family and cultural environment, leading to women to have fear, isolation, depression, anxiety and other mental disorders.